Babylonian Jews and Sasanian imperialism in late antiquity - Gross, Simcha (Cambridge University Press, 2024)
From the image offered by the Babylonian Talmud, Jewish elites were deeply embedded within the Sasanian Empire (224-651 CE). The Talmud is replete with stories and discussions that feature Sasanian kings, Zoroastrian magi, fire temples, imperial administrators, Sasanian laws, Persian customs, and more quotidian details of Jewish life. Yet, in the scholarly literature on the Babylonian Talmud and the Jews of Babylonia , the Sasanian Empire has served as a backdrop to a decidedly parochial Jewish story, having little if any direct impact on Babylonian Jewish life and especially the rabbis. Babylonian Jews and Sasanian Imperialism in Late Antiquity advances a radically different understanding of Babylonian Jewish history and Sasanian rule. Building upon recent scholarship, Simcha Gross portrays a more immanent model of Sasanian rule, within and against which Jews invariably positioned and defined themselves. Babylonian Jews realized their traditions, teachings, and social position within the political, social, religious, and cultural conditions generated by Sasanian rule